PWE-163 Factors predicting extended length of stay following laparoscopic Nissen fundoplication: a move towards day case surgery. (28th May 2012) - Alkhaffaf, B; Turner, P; Date, R; Mughal, M; Ward, J; Pursnani, K
Abstract : Introduction: There has been a move towards performing laparoscopic gastric fundoplication as a "day-case" procedure. This study aimed to determine which factors influence length of stay (LOS) to better enable patient selection for "day-case" fundoplication. Methods: This was a retrospective study of 229 consecutive laparoscopic Nissen fundoplications performed between 1999 and 2011. The primary outcome measure was length of hospital stay (LOS). Factors examined were patient age, main indication for surgery (large hiatus hernia or gastro-oesophageal reflux disease (GORD) and primary or redo surgery), history of previous surgery and presence and size of hiatus hernia. Results: Patients undergoing surgery for large hiatus herniae had an average 2-day greater LOS compared to those undergoing surgery for GORD (p<0.001). Surgery for large hiatus herniae was also associated with a higher rate of conversion to open surgery (41% vs 7%; p<0.001). LOS was not affected by small or moderate sized hiatus herniae. A history of previous open upper abdominal surgery increased LOS by an average of 2 days (p=0.010) and was associated with a higher rate of conversion to open surgery when compared to cases with no past surgical history (40% vs 12.7%; p=0.036). Redo fundoplication surgery led to an increased LOS by an average of 1.5 days (p=0.044) when compared to primary surgery. There was a positive correlation between age and LOS (p=0.007). Conclusion: Factors which should exclude patients from undergoing "day-case" fundoplication include; large hiatus hernia as the main indication for intervention, redo surgery, a history of previous open upper abdominal surgery and advancing age. Competing interests: None declared.